Positional and match action profiles of elite women`s field hockey players in relationship to the 2015 FIH rule changes - Abbott, H. A. (Electronic Theses and Dissertations, 3092, 2016)
The objective of this dissertation was to examine the action profiles of elite field hockey players in relationship to the 2015 FIH rule change. The following are major findings of the dissertation: The following are major findings of the dissertation: Study 1 - Relative action profiles before the rule change revealed that defenders work at a lower meter per minute (m/min) when compared with all other positions, and that forwards, midfielders, and screens perform similar m/min during a game. Examination of pre rule change difference from the 1st to the 2nd half play showed that elite level field hockey players are able maintain high-intensity actions in zone 6 throughout the game by increasing actions in zones 1 and 2, and decreasing actions in zones 4 and 5. Study 2 - Action profiles after the rule formatting change revealed the team was unable to match the percent of distance covered in zones 4 and 5 during the 1st quarter all in subsequent quarters. The low intensity actions in zone 1 and 2 gradually increased, while m/min gradually declined. However the percent of distance covered in zone 6 showed no statistically significant change. When positional differences were examined forwards covered the greatest percent of distance in zones 5 and 6, followed by midfielders, screens, and defenders. This pattern varies for zone 4, within which the midfielders possesses the greatest percent distance covered. 3 Study 3 - Relative action profile comparisons for the team, pre to post the 2015 rule change did not indicate a significant change in zones 2, 3, 4, 5, and 6. However zone 1 experience a statistically significant decrease. Positional analysis showed statistically significant changes for midfielders only. The changes were a decrease in zone 1, and increase in zone 5 and 6 during the first half of the game, and decrease in zone 1 and m/min during the second half of the game. A major focus of the US Women`s National Team is to develop the athletes` physical capacity to maintain and repeat high intensity actions. The combination of physical preparation and tactical strategies allow the team to express high m/min and numerous high intensity actions throughout a match.